2012
DOI: 10.3892/mmr.2012.856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Panax notoginseng flower extract on the TGF-β/Smad signal transduction pathway in heart remodeling of human chymase transgenic mice

Abstract: Abstract. Panax notoginseng is a common Chinese herb extensively used in Chinese medical practice for the treatment of cardiovascular diseases. The present study aimed to evaluate the effects of Panax notoginseng flower extract (PNFE) on the TGF-β/Smad signal transduction pathway in heart remodeling of human chymase transgenic mice. After treatment with PNFE and soybean trypsin inhibitor (SBTI), the left ventricular mass indexes (LVMIs) of transgenic and normal C57 BL/6 mice were analyzed. The mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Various phytochemical and pharmacological investigations have been performed on ginseng, and the root of ginseng is considered to be the most active part of the ginseng plant. In recent years, growing research indicates that other parts of the ginseng plant including berries, leaves, and flower buds also have potential therapeutic activities [1] , [2] , [3] , [4] . However, there is considerably less experimental evidence regarding the medicinal properties of ginseng seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Various phytochemical and pharmacological investigations have been performed on ginseng, and the root of ginseng is considered to be the most active part of the ginseng plant. In recent years, growing research indicates that other parts of the ginseng plant including berries, leaves, and flower buds also have potential therapeutic activities [1] , [2] , [3] , [4] . However, there is considerably less experimental evidence regarding the medicinal properties of ginseng seeds.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies used root extracts from ginseng species, floral extracts of P notoginseng have also been shown to exert antihypertrophic effects. Thus, a P notoginseng flower extract administered to chymase-overexpressing transgenic mice effectively reduced the resultant hypertrophic and remodeling effects through a mechanism associated with reduced expression of chymase, transforming growth factor beta (TGF- 1), Smad2 and Smad3 while upregulating expression levels of Smad7 [ 18 ]. P notoginseng , therefore, appears to be an effective antihypertrophic agent acting primarily through its constituent notoginsenosides.…”
Section: Antihypertrophic Effects Of Ginseng and Ginsenosidesmentioning
confidence: 99%
“…A summary of the effects of ginseng and ginsenosides and their proposed underlying mechanisms is presented in Table 1 (Ref. [ 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 24 , 27 , 28 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]).…”
Section: Antihypertrophic Effects Of Ginseng and Ginsenosidesmentioning
confidence: 99%
“…These saponins could attenuate inflammatory response [12], inhibit proliferation [13], and enhance both sperm motility and sperm progression [14]. More importantly, it was found PN-F had stronger angiogenesis effects on zebrafish than roots [15] and improved the ventricular hypertrophy state in human chymase transgenic mice through regulation of the expression of mRNA and protein of TGF-β/Smad in ventricular tissues [16]. Furthermore, our previous results demonstrated that the purified saponin preparation from PN-F could ameliorate acute myocardial infarction via proangiogenesis and antiapoptosis [1719].…”
Section: Introductionmentioning
confidence: 99%